If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -3) + 2 = 3x + 2(-5 + x) Reorder the terms: 5(-3 + x) + 2 = 3x + 2(-5 + x) (-3 * 5 + x * 5) + 2 = 3x + 2(-5 + x) (-15 + 5x) + 2 = 3x + 2(-5 + x) Reorder the terms: -15 + 2 + 5x = 3x + 2(-5 + x) Combine like terms: -15 + 2 = -13 -13 + 5x = 3x + 2(-5 + x) -13 + 5x = 3x + (-5 * 2 + x * 2) -13 + 5x = 3x + (-10 + 2x) Reorder the terms: -13 + 5x = -10 + 3x + 2x Combine like terms: 3x + 2x = 5x -13 + 5x = -10 + 5x Add '-5x' to each side of the equation. -13 + 5x + -5x = -10 + 5x + -5x Combine like terms: 5x + -5x = 0 -13 + 0 = -10 + 5x + -5x -13 = -10 + 5x + -5x Combine like terms: 5x + -5x = 0 -13 = -10 + 0 -13 = -10 Solving -13 = -10 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2+(x+4)+8x=8 | | f(x)=-4x^2-9x-4 | | -5-(-30)=x/9 | | -5(4y-6)-y=-2(y-3) | | 4t-8=10 | | -4(8x+5)-6=-32x-26 | | 11.7+x-8.4=3.7 | | 4(5x-10)=20(x-10) | | 2(tx-8)-4x=10 | | 6(5k-3)=8k+4 | | (x+4)(x-1)=36 | | 5n^2+45n=0 | | -3.9=12.1-4y | | vf=vi-gt | | 54x-40=7(7x-6)+5x+2 | | Xy+3x=6 | | 26x+15=5(5x+4) | | 22-v/3=-7 | | -10+x-9=11-15+5 | | 2x-(15-7x)=120 | | 5-(-2y+2)= | | (3x-10)(x+40)=180 | | 5(2x-1)-2(3x+4)=3 | | 4(x-1)-1=2x+2(-1+x) | | 2x+5=5+3x-1 | | X^(1/2)=8.1 | | (3x-10)+(x+40)=180 | | 17+5y-2=15y-9-2y | | 3x-27+12-62= | | X^1/2=8.1 | | -7.7(6.71x-0.4)=101.2473 | | 21(2+x)+12=44 |